2011
DOI: 10.1002/jcc.21895
|View full text |Cite
|
Sign up to set email alerts
|

Zinc–Homocysteine binding in cobalamin‐dependent methionine synthase and its role in the substrate activation: DFT, ONIOM, and QM/MM molecular dynamics studies

Abstract: Cobalamin-dependent methionine synthase (MetH) is an important metalloenzyme responsible for the biosynthesis of methionine. It catalyzes methyl transfer from N(5)-methyl-tetrahydrofolate to homocysteine (Hcy) by using a zinc ion to activate the Hcy substrate. Density functional theory (B3LYP) calculations on the active-site model in gas phase and in a polarized continuum model were performed to study the Zn coordination changes from the substrate-unbound state to the substrate-bound state. The protein effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…At present, QM/MM method and MD simulations have been combined to successfully study the inhibitorprotein interactions, functions of metalloproteins, and enzyme catalysis (Abdel-Azeim, Li, Chung, & Morokuma, 2011;Chen, Liang, Wang, Yi, Zhang, & Zhang, 2014;Duan, Mei, Zhang, Zhang, & Zhang, 2010;Duan, Mei, Zhang, & Zhang, 2009;Fan, Cembran, Ma, & Gao, 2013;Gao, Lu, Duan, Zhang, & Mei, 2011;Hou & Cui, 2013;Hou, McLaughlin, & Wang, 2007;Hu, Zhu, Zhang, Wang, & Zhang, 2010;Hu & Wang,2014;Ke, Wang, Xie, & Zhang, 2009;Keerthana & Kolandaivel, 2014;Meher, Kumar, & Bandyopadhyay, 2014;Smith, Ke, Guo, & Hengge, 2011;Wang et al, 2010Wang et al, , 2013Wang, Wu, Xu, Xie, & Guo, 2011;Wong, Richard, & Gao, 2009;Zhu, He, & Zhang, 2012;Zhu, Xiao et al, 2013). This method can take the polarizable electrostatic effect into account explicitly and accurately treat hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 97%
“…At present, QM/MM method and MD simulations have been combined to successfully study the inhibitorprotein interactions, functions of metalloproteins, and enzyme catalysis (Abdel-Azeim, Li, Chung, & Morokuma, 2011;Chen, Liang, Wang, Yi, Zhang, & Zhang, 2014;Duan, Mei, Zhang, Zhang, & Zhang, 2010;Duan, Mei, Zhang, & Zhang, 2009;Fan, Cembran, Ma, & Gao, 2013;Gao, Lu, Duan, Zhang, & Mei, 2011;Hou & Cui, 2013;Hou, McLaughlin, & Wang, 2007;Hu, Zhu, Zhang, Wang, & Zhang, 2010;Hu & Wang,2014;Ke, Wang, Xie, & Zhang, 2009;Keerthana & Kolandaivel, 2014;Meher, Kumar, & Bandyopadhyay, 2014;Smith, Ke, Guo, & Hengge, 2011;Wang et al, 2010Wang et al, , 2013Wang, Wu, Xu, Xie, & Guo, 2011;Wong, Richard, & Gao, 2009;Zhu, He, & Zhang, 2012;Zhu, Xiao et al, 2013). This method can take the polarizable electrostatic effect into account explicitly and accurately treat hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Biochemists continue to isolate zinc metalloenzymes relevant to mammalian biology which conform with the Parisi-Vallee postulates [6]. Table 1 illustrates several of the enzymes most recently identified as zinc metalloenzymes in the continuing elucidation of their extent and functions in nature [7,8,9]. Meanwhile, studies on the active site of carbonic anhydrase, the first of the zinc metalloenzymes identified, and its mode of operation continue to advance six decades later [10].…”
Section: Organic Chemistry Of Zincmentioning
confidence: 99%
“…The geometries of interested species were fully optimized in conjunction with the SMD 36 continuum solvation model at the B3LYP/def2-SVP level of theory. B3LYP was proven to be a successful functional for studying zinc-based metalloenzymes 37 39 . The energies were further refined with the larger basis set def2-TZVP for all atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the electronic embedding scheme 43 was employed to account for the polarizing effect of the enzyme environment on the QM region, while the hydrogen link atoms with the charge-shift model was used to deal with the QM/MM boundary. Here, the QM region was studied with the hybrid B3LYP 44 , 45 density functional, which has been proven to be reliable for the simulation of zinc-containing metalloenzymes 37 , 39 , 46 , 47 . In this study, the double-ζ basis set def2-SVP were used for geometry optimization, while the energies were corrected with the larger basis set def2-TZVP for all the QM region atoms.…”
Section: Methodsmentioning
confidence: 99%